Protease Inhibitors from Solanum chacoense Inhibit Pectobacterium Virulence by Reducing Bacterial Protease Activity and Motility - Janak R. Joshi; Kitty Brown; Amy O. Charkowski; Adam L. Heuberger (Molecular Plant-Microbe Interactions, 2022)
Potato is a major staple crop, and necrotrophic bacterial pathogens such as Pectobacterium spp. are a major threat to global food security. Most lines of cultivated potato (Solanum tuberosum) are susceptible to Pectobacterium spp., but some lines of wild potato are resistant, including Solanum chacoense M6. Despite the discovery of resistance in wild potatoes, specific resistance genes are yet to be discovered. Crude protein extract from M6 had a global effect on Pectobacterium brasiliense Pb1692 (Pb1692) virulence phenotypes. Specifically, M6 protein extracts resulted in reduced Pectobacterium exo-protease activity and motility, induced cell elongation, and affected bacterial virulence and metabolic gene expression. These effects were not observed from protein extracts of susceptible potato S. tuberosum DM1. A proteomics approach identified protease inhibitors (PIs) as candidates for S. chacoense resistance, and genomic analysis showed higher abundance and diversity of PIs in M6 than in DM1. We cloned five PIs that are unique or had high abundance in M6 compared with DM1 and purified the proteins (g18987, g28531, g39249, g40384, g6571). Four of the PIs significantly reduced bacterial protease activity, with strongest effects from g28531 and g6571. Three PIs (g18987, g28531, g6571) inhibited disease when co-inoculated with Pectobacterium pathogens into potato tubers. Two PIs (g28531, g6571) also significantly reduced Pb1692 motility and are promising as resistance genes. These results show that S. chacoense PIs contribute to bacterial disease resistance by inhibiting exo-proteases, motility, and tuber maceration and by modulating cell morphology and metabolism. [Graphic: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.